ANALYSIS OF WRITING SKILLS OF GRADE 10 STUDENTS AT BATIK 2 SURAKARTA HIGH SCHOOL ON ENGLISH DESCRIPTIVE TEXT - Hilmy Rasyid Hilmy Rasyid; Rini Fatmawati (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to analyze the ability of tenth-grade students at SMA Batik 2 Surakarta in writing English descriptive texts using Heaton's framework. The study evaluates five aspects: content, organization, grammar, vocabulary, and mechanics. Using a descriptive quantitative method, students were given a descriptive writing test and assessed based on Heaton’s rubric. The results show that most students fall into the Good to Average category across all indicators. However, grammar, organization, and mechanics remain the most challenging areas. Vocabulary and content are relatively well-mastered. These findings suggest the need for more structured instruction in grammar and writing conventions.